Perfil temporal e mecanismos de hiperatividade simpática após ligadura da artéria coronária na preparação tronco cerebral-coração isolados de ratos - Passamani, Luciana Mesquita (2014)
Methods and Results: The working heart brainstem preparation was used to record phrenic and thoracic sympathetic (tSNA) nerves activities, heart rate (HR), electrocardiogram (ECG) and perfusion pressure of Wistar rats. The ligation of the left anterior descending coronary artery (LAD) (LAD group) or “fictitious ligation” (Sham group) was performed in vitro. The myocardial area at risk was 36.3 ± 1.1% of the left ventricle and it was assessed post-hoc with Evans blue dye at the end of the experiment; no area at risk was observed in Sham group. Recordings were evaluated over the course of one hour post LAD ligation or “fictitious ligation” and there was an increased tSNA within 30 min, reaching even higher levels at 60 min in LAD group (basal: 2.5 ± 0.2, 30 min: 3.5 ± 0.3, 60 min: 5.2 ± 0.5 µV, P<0.01 versus Sham group – basal: 2.2 ± 0.3, 30 min: 2.2 ± 0.3, 60 min: 2.3 ± 0.3 µV, P>0.05). HR increased 45 min post LAD ligation (P<0.01 compared to basal); there was no HR changes in Sham group. The reflex and tonic autonomc function were assessed 60 minutes post LAD ligation or “fictitious ligation” and there was: (i) A greater sympathoexcitatory chemoreflex response to three different doses of NaCN (0.03 % – 25, 50 and 75 µL: 49.7, 45.3 and 26.8 % of increase, respectively, compared to similar doses in Sham, P<0.01). (ii) An elevated pressor response (LAD 31.5 ± 1.3 versus Sham 23.1 ± 1.2 mmHg, P<0.01) and depressed sympathetic baroreflex gain (LAD 1.3 ± 0.1 versus Sham 2.0 ± 0.1 %.mmHg-1, P<0.01) to phenylephrine. (iii) An elevated cardiac sympathetic tone (changes in HR after atenolol: LAD -107.8 ± 8.0 versus Sham -81.6 ± 7.4 bpm, P<0.05). (iv) In contrast, there were no changes in cardiac vagal tone and bradycardic response to both the baroreflex and chemoreflex between LAD and Sham groups. The investigation of mechanisms driving up sympathoexcitation showed: (v) The involvement of angiotensin type 1 receptor sustaining sympathoexcitation, since losartan blockade blunted tSNA at 3 h after LAD ligation (33.8 % of attenuation compared to Control Saline-LAD group, P<0.05). (vi) The role of spinal sympathetic cardiocardiac reflex mediating the initial changes in sympathetic activity, because spinal transected rats still presented sympathetic over activity post LAD ligation. Conclusion: The sympathetic nervous system is activated immediately after coronary ligation in the rat, being mediated by spinal mechanisms and, later, sustained by angiotensinergic mechanisms and concomitant augmentation of sympathoexcitatory reflexes.